Elementos Determinantes en la Comercialización de Panela Pulverizada en el Departamento del Huila: Una Propuesta Exportable hacia Mercados Internacionales (2023)
The purpose of this monograph is to address the determining elements for the commercialization of powdered panela in Huila, Colombia, in the international market, with a focus on its viability as an exportable product to international markets. Documentary research is conducted to analyze elements related to production, exports, distribution logistics, and other relevant aspects. The study aims to understand how these local and global factors impact the marketing of powdered panela and how they can enhance the competitiveness of local producers in international markets.